Preliminary Biological Study of Two Medicinal Plants used in the Mouhoun Region (Burkina Faso): Boscia angustifolia A. Rich (Caparaceae) and Gardenia erubescens Stapf & Hutch (Rubiaceae) - Jotham Yhi-Pênê N’do; Dramane Pare; Mahamadi Nikiema; Adama Hilou (Archives of Current Research International, 2019)
Aims: Boscia agustifolia and Gardenia erubescens are two medicinal plants widely used in the Mouhoun region. The strong use of these two plants in traditional medicine would be linked to their therapeutic virtues. Study Design: The purpose of this work was to carry out a preliminary biological study on two plants widely used by the population of the Mouhoun region (Burkina Faso) against certain diseases. Place and Duration of Study: The harvest of plant material was made in the Mouhoun region in March 2019. The phytochemistry and the antioxidant tests were carried out at LABIOCA in June 2019. The microorganism tests were carried out at CRSBAN. Methodology: The extracts were obtained by ethanolic maceration. The FRAP method and DPPH were used to evaluate the antioxidant properties of the extracts. The antibiomicrobial activity of the extracts was determined using five microbial strains. Results: The ethanolic extract of Gardenia erubescens bark had antioxidant activity through the iron ion reduction capacity (6.71 ± 1.16 mMol EAA/100 g extract. Boscia angustifolia showed inhibitory activity on the five microbial strains. Conclusion: The biological activities obtained with these extracts could be justified by the presence of active phytochemicals such as flavonoids. These biological properties to constitute a reason based on the strong use of these two plants in traditional medicine.